Analysis and inactivation of vha55, the gene encoding the vacuolar ATPase B-subunit in Drosophila melanogaster reveals a larval lethal phenotype. - Davies, SA; Goodwin, S; Kelly, D; Wang, Z; Sözen, M; Kaiser, K; Dow, J (1996)
Vacuolar ATPases play major roles in endomembrane and plasma membrane proton transport in eukaryotes. A Drosophila melanogaster cDNA encoding vha55, the 55-kDa vacuolar ATPase (V-ATPase) regulatory B-subunit, was characterized and mapped to 87C2-4 on chromosome 3R. A fly line was identified that carried a single lethal P-element insertion within the coding portion of gene, and its LacZ reporter gene revealed elevated expression in Malpighian tubules, rectum, antennal palps, and oviduct, regions where V-ATPases are believed to play a plasma membrane, rather than an endomembrane, role. The P-element vha55 insertion was shown to be allelic to a known lethal complementation group l(3)SzA (= l(3)87Ca) at 87C, for which many alleles have been described previously. Deletions of the locus have been shown to be larval lethal, whereas point mutations show a range of phenotypes from subvital to embryonic lethal, implying that severe alleles confer a partial dominant negative phenotype. The P-element null allele of vha55 was shown also to suppress ectopic sex combs in Polycomb males, suggesting that transcriptional silencing may be modulated by genes other than those with known homeotic or DNA binding functions.